Harnessing ynamide activation to access deuterated carbonyls. (18th June 2021) - Porte, Vincent; Zhang, Haoqi; Kaiser, Daniel; Maulide, Nuno
Abstract: A simple and convenient synthesis of α-bisdeuterated imides is reported, hinging on the transient formation of keteniminium ions by treatment of ynamides with TfOD, followed by trapping with D2 O. The products are obtained in good yields and with a high degree of deuterium incorporation. Gram-scale reaction and further derivatization without deuterium erosion highlight the synthetic utility of this method for the formation of a wide range of isotopically labelled compounds. Graphical abstract: Image 1